The Effect of Nursing Supervision Based on Proctor's Model on Improving the Quality of Nursing Work Life of Nurses after Nurse Rotation - Achmani, Anik; Lestari, Indah; Rahmawati, Ima; Saudah, Noer; Rusdi, Ainur (GLOBAL HEALTH SCIENCE GROUP, 2024)
Nurse rotation is a process of dynamically replacing scheduled nurses from one department to another. Job rotation can have a negative impact on nurses including feelings of anxiety, anger, fear, frustration, sadness, and nurses must begin to adapt to a new environment where this can reduce nurse satisfaction so that it can reduce the quality of work of nurses in providing nursing care. Objective: To analyze the effect of nursing supervision based on proctor's model on improving the quality of nursing work life of nurses after nurse rotation at RSUD dr. Soetomo Surabaya. Methods: This research design is a pre-experimental research method one-group pre-posttest design. The sample in this study were 30 nurses who were carried out nurse rotation using total sampling technique. Research data were collected through the QNWL questionnaire. Data were analyzed using the Wilcoxon signed rank test statistical test. Results: The results showed that the results of statistical test analysis with Wilcoxon on the Quality of Nursing Work Life variable (Work life home life, Work design, Work context, and Work world produced a significance value < alpha (5% or 0.05). Conclusion: There is a significant effect of nursing supervision based on proctor's model on improving the quality of nursing work life of nurses after nurse rotation at RSUD dr. Soetomo Surabaya. It is expected that the head of the room to supervise the nurses regularly and scheduled so that they can find out the various problems experienced by nurses, especially regarding the QNWL of nurses so that they can improve the performance of nurses which in turn can improve the quality of nursing care.